The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1021/acs.jchemed.7b00832
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Paper Model Illustrates How To Cyclize Monosaccharides from Fischer Projections to Haworth

Abstract: Turning a linear sugar into its cyclized form is an essential skill in biochemistry. A simple paper model is described that can be used by any student to transform a carbohydrate in its Fischer projection and correctly cyclize it into its Haworth form. The model can also be used to illustrate several key aspects of the Fischer projection of which many students are typically unaware.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The author was inspired to develop papercraft models by Kondinski’s reports. Paper crafts have been reported that allow students to learn about the structures of sugars and fullerenes. , The papercraft models are inexpensive and easy to build because they are made from paper and simple materials. For molecular cage models, the coordination bonds are represented by clips, which, while it increases the work process and difficulty of the craft, also increases the fun of assembling them.…”
Section: Resultsmentioning
confidence: 99%
“…The author was inspired to develop papercraft models by Kondinski’s reports. Paper crafts have been reported that allow students to learn about the structures of sugars and fullerenes. , The papercraft models are inexpensive and easy to build because they are made from paper and simple materials. For molecular cage models, the coordination bonds are represented by clips, which, while it increases the work process and difficulty of the craft, also increases the fun of assembling them.…”
Section: Resultsmentioning
confidence: 99%
“…Typically, carbohydrates are presented in biochemistry courses as chemical structures-often Fischer or Haworth projections. Despite the popular use of these representations, it is notoriously difficult for students to extract stereochemical information from them [43], which suggests that 3D molecular representations should be more widely used in instruction.…”
Section: Rq1: Which Assessment Items Exhibit Statistically Significan...mentioning
confidence: 99%
“…Stereochemistry is the branch of chemistry that studies the three-dimensional (3D) structure of organic compounds and the impact of spatial arrangements of atoms on the stability and reactivity of compounds. , Different molecular representations, such as the zigzag structure (Natta projection), Newman projection, and Fischer projection, have been developed to depict the three-dimensional (3D) structure of organic compounds. Converting one molecular representation into another is among the main learning objectives of an introductory organic chemistry course. , Mastering the skill of converting one molecular representation into another requires understanding the 3D structure of each form, performing the necessary operations to complete the transformation, and then executing it. Three-dimensional visualization of molecules is essential for chemistry-major students; however, for nonmajors or students with a certain level of aphantasia, this can be difficult and overwhelming. , Using model kits or computer software can help in 3D visualization; however, such techniques are only reliable in classroom activities involving small molecules and are impractical for large molecules or during exams. , Despite the importance of this topic, interconverting the different molecular representations has received little attention in undergraduate organic chemistry textbooks, , and the development of simple, practical, and student-friendly techniques remains necessary. Several methods have been reported for the interconversion of the different molecular representations. , However, only a few have been reported about interconverting zigzag structures and Fischer projections. , The traditional approaches for completing such interconversions that involve drawing the fully eclipsed conformation, using the “absolute configuration assignment” method, or 3D visualization are usually time-consuming and impractical, especially for compounds with multiple chiral centers. In this context, Mandal described a method for converting the 3D bond-line structure of a chiral center into a Fischer projection to facilitate absolute configuration assignment .…”
Section: Introductionmentioning
confidence: 99%